2019
DOI: 10.1002/adfm.201807857
|View full text |Cite
|
Sign up to set email alerts
|

Attractive In Situ Self‐Reconstructed Hierarchical Gradient Structure of Metallic Glass for High Efficiency and Remarkable Stability in Catalytic Performance

Abstract: Metallic glass (MG), with the superiorities of unique disordered atomic structure and intrinsic chemical heterogeneity, is a new promising and competitive member in the family of environmental catalysts. However, what is at stake for MG catalysts is that their high catalytic efficiency is always accompanied by low stability and the disordered atomic configurations, as well as the structural evolution, related to catalytic performance, which raises a primary obstacle for their widespread applications. Herein, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…As shown in Fig. 7f, the E a of the Fe-MGI catalyst in this work is 34.2 kJ mol −1 , a value lower than observed for crystalline alloys and comparable to those of MG catalysts [40]. After comparing the degradation efficiencies and k obs in MB dye solutions with or without the Fe-MGI catalyst, in the presence of different H 2 O 2 concentrations, dye concentrations, temperatures, and pH values, it can be concluded that Fe-MGI shows good catalytic properties for Fenton-like processes in acid solutions.…”
Section: Catalytic Propertiessupporting
confidence: 54%
See 1 more Smart Citation
“…As shown in Fig. 7f, the E a of the Fe-MGI catalyst in this work is 34.2 kJ mol −1 , a value lower than observed for crystalline alloys and comparable to those of MG catalysts [40]. After comparing the degradation efficiencies and k obs in MB dye solutions with or without the Fe-MGI catalyst, in the presence of different H 2 O 2 concentrations, dye concentrations, temperatures, and pH values, it can be concluded that Fe-MGI shows good catalytic properties for Fenton-like processes in acid solutions.…”
Section: Catalytic Propertiessupporting
confidence: 54%
“…The durability of the present , temperature of 25°C. system is even more stable than those of the most recently reported Fe-MGs with excellent sustainability that can be reused about 35 times [40]. Therefore, Fe-MGI shows sustainable long-term high reactivity.…”
Section: Long-term Reactivitymentioning
confidence: 84%
“…Chemically complex catalytic materials have been the subject that attracts tremendous research interest in materials science and engineering. [ 1–3 ] By increasing the chemical complexity of modern catalytic materials, it has been shown that superior properties could be achieved for their use in a variety of important applications, such as wastewater remediation, [ 4–8 ] catalysis, [ 9,10 ] energy storage, [ 11 ] and fuel cells. [ 12 ] Recently, a similar design principle was proposed by metallurgists to enhance the chemical complexity of alloys through the synthesis of multi‐principal element alloys, also known as high entropy alloys (HEAs), [ 13,14 ] for enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike their crystalline counterparts, metallic glasses do not possess defects like grain boundaries and dislocations [1][2][3][4][5][6][7]. Therefore, they show specific mechanical, chemical and physical properties, such as high strength, high hardness and good corrosion resistance [1,4,[8][9][10][11]. As a consequence, metallic glasses are great functional and structural materials from a point of practical application.…”
Section: Introductionmentioning
confidence: 99%